Shawqi between Mandour and Al-Akkad: A critical view - Al-Sarahneh, Sara Hussein (Journal of Arabic Language Sciences and Literature, 2022)
This research dealt with a critical topic, which is “Shawqi between Mandour and Al-Akkad.” The importance of the topic that criticism was the beginning establishing criticism rules in this field especially since they are of the big and great critic and modern age, Shawqi is age poet.This research aimed at showing how Shawqi was criticized by Muhammad Mandour and Al-Akkad, and what is Shawqi's position on this criticism.When the great critics meet, the conversation becomes meaningful, and a good approach that yields the opinions and comments of those critics, because they are the way to develop proper, correct and impartial literature.The importance of this research lies in highlighting the role of literary criticism through great critics of a poet like Shawqi. My only motivation was to see the critical study in place; because criticism is one of the best means of changeThe focus of criticism which the study revolves around an idea that can be developed by the students. My goal was to present this creative critical idea and treat it. One of the main reasons for choosing this research was the role of literary criticism in treating many literary problems and offering solutions to them, by presenting the two points of view between Mandour and Al-Akkad for Shawqi.As well as answering the following questions:1. Have modern critical studies been able to solve the major problem of stumbling among contemporary writers, or have they failed to solve or eliminate it? 2. Have Mandour and Al-Akkad really pushed the status of literary criticism to the required levels?I balanced between Al-Akkad and Mandour's criticism of Shawqi's poetry, each of them's vision of his lyrical theatrical poetry, the content of his literary work and the drawbacks that Al-Akkad took on him, and Mandour's just judgment of him.
Keywords: Arabic poetry; Ahmed Shawki; Muhammad Mandour; Al-Akkad; criticism